Latino small businesses and the American dream : community social work practice and economic and social development - Delgado, Melvin (Columbia University Press, 2011)
Latino small businesses provide social, economic, and cultural comfort within their communities. Social work practitioners hoping to address such needs, not only among Latinos but in all communities of color, have a vested interest in seeing these businesses grow. Latino small businesses are excellent facilitators of community capacity, a major component of effective social work practice. Reviewing the latest research on formal and informal economies within urban communities of color, this book lays the demographic foundations for a richer collaboration between theory and practice.<b.